Computing the Constant Elasticity of Variance Option Pricing Formula - Schröder, Mark (Journal of Finance, 1989)
This paper expresses the constant elasticity of variance option pricing formula in terms of the noncentral chi-square distribution. This allows the application of well-known approximation formulas and the derivation of a whole class of closed-form solutions. In addition, a simple and efficient algorithm for computing this distribution is presented.